Cytochrome P450 Monooxygenase/Cytochrome P450 Reductase Bi-Enzymatic System Isolated From Ilex asprella for Regio-Specific Oxidation of Pentacyclic Triterpenoids - Li, Le; Lin, Shumin; Chen, Yuanyuan; Wang, Yaqin; Xiao, Luhua; Ye, Xiaofang; Sun, Lei; Zhan, Ruoting; Xu, Hui (Frontiers in Plant Science, 2022)
Ilex asprella is a plant of Ilex genus in Aquifoliaceae. Its root is commonly used as folk medicinal materials in southern China. The chemical compositions of I. asprella are rich in triterpenoids, which has a good drug development prospect. Therefore, studying the biosynthesis mechanism of triterpenoids in I. asprella is expected to obtain the biological elements required for the synthesis of triterpenes and lays a foundation for subsequent metabolic engineering. Herein, we reported the identification of three cytochrome P450 monooxygenase genes IaAO2, IaAO4 and IaAO5 and a cytochrome P450 reductase gene IaCPR by using Saccharomyces cerevisiae eukaryotic expression system and gas chromatography-mass spectrometry. Among them, the protein encoded by IaAO2 can catalyze the C-28 oxidation of α-amyrin and β-amyrin, IaAO4 can catalyze the C-23 oxidation of ursolic acid and oleanolic acid, while IaAO5 can catalyze the C-24 oxidation of β-amyrin. In addition, we also constructed an engineered strain of S. cerevisiae that can produce C-23 hydroxyl ursane triterpenoid using three genes involved in triterpenoid biosynthesis from I. asprella including IaAO4. This study contributes to a thorough understanding of triterpenoid biosynthesis of medicinal plants and provides important tools for further metabolic engineering.